Defining gene signature underlying impaired hippocampal neurogenesis in triple transgenic Alzheimer’s disease mice - Ng, Yi Lin (2016)
Using triple-transgenic (3xTg) Alzheimer’s disease (AD) mouse model that carries mutations in APP, p-Tau and PS1, we provided evidence to show that soluble Aβ and APP are accumulated in the hippocampus of AD mice by 1.5 months of age. In addition, impaired neurogenesis was also detected in the dentate gyrus (DG) of the hippocampus in 3xTg-AD mice in 1.5 months-old. Specifically, we showed a reduced neuronal proliferative capacity by BrdU immunostaining and a decreased cell survivability by DCX immunostaining in the DG of AD mice, compared to wild type (WT) mice; whereas, neural differentiation rate remains unaffected. Furthermore, the decreased proliferation in AD at an early stage may be influenced by the expression of APP intracellular domain (AICD)-mediated target genes, such as FBXL18, PTP4A1, and CDK6. FBXL18 and PTP4A1 were shown to be down-regulated at 1.5 month-old, compared to the WT mice; whereas, CDK6 was found to be up-regulated in the AD mice. These findings provide evidence that decreased neural proliferation in early AD could be regulated through FBXL18, CDK6 and PTP4A1. Therefore, targeting these genes may provide therapeutic potential to treat the neurogenesis-associated cognitive decline in AD.